Engineering Posttranslational Regulation of Glutamine Synthetase for Controllable Ammonia Production in the Plant Symbiont Azospirillum brasilense - Schnabel, Tim; Sattely, Elizabeth (Applied and environmental microbiology, 2021)
Nitrogen is the most limiting nutrient in modern agriculture. Free-living diazotrophs, such as Azospirillum , are common colonizers of cereal grasses and have the ability to fix nitrogen but natively do not release excess ammonia. Nitrogen requirements for modern agriculture far exceed the levels of bioavailable nitrogen in most arable soils. As a result, the addition of nitrogen fertilizer is necessary to sustain productivity and yields, especially for cereal crops, the planet’s major calorie suppliers. Given the unsustainability of industrial fertilizer production and application, engineering biological nitrogen fixation directly at the roots of plants has been a grand challenge for biotechnology. Here, we designed and tested a potentially broadly applicable metabolic engineering strategy for the overproduction of ammonia in the diazotrophic symbiont Azospirillum brasilense . Our approach is based on an engineered unidirectional adenylyltransferase (uAT) that posttranslationally modifies and deactivates glutamine synthetase (GS), a key regulator of nitrogen metabolism in the cell. We show that this circuit can be controlled inducibly, and we leveraged the inherent self-contained nature of our posttranslational approach to demonstrate that multicopy redundancy can improve strain evolutionary stability. uAT-engineered Azospirillum is capable of producing ammonia at rates of up to 500 μM h −1 unit of OD 600 (optical density at 600 nm) −1 . We demonstrated that when grown in coculture with the model monocot Setaria viridis , these strains increase the biomass and chlorophyll content of plants up to 54% and 71%, respectively, relative to the wild type (WT). Furthermore, we rigorously demonstrated direct transfer of atmospheric nitrogen to extracellular ammonia and then plant biomass using isotopic labeling: after 14 days of cocultivation with engineered uAT strains, 9% of chlorophyll nitrogen in Setaria seedlings was derived from diazotrophically fixed dinitrogen, whereas no nitrogen was incorporated in plants cocultivated with WT controls. This rational design for tunable ammonia overproduction is modular and flexible, and we envision that it could be deployable in a consortium of nitrogen-fixing symbiotic diazotrophs for plant fertilization. IMPORTANCE Nitrogen is the most limiting nutrient in modern agriculture. Free-living diazotrophs, such as Azospirillum , are common colonizers of cereal grasses and have the ability to fix nitrogen but natively do not release excess ammonia. Here, we used a rational engineering approach to generate ammonia-excreting strains of Azospirillum . Our design features posttranslational control of highly conserved central metabolism, enabling tunability and flexibility of circuit placement. We found that our strains promote the growth and health of the model grass S. viridis and rigorously demonstrated that in comparison to WT controls, our engineered strains can transfer nitrogen from 15 N 2 gas to plant biomass. Unlike previously reported ammonia-producing mutants, our rationally designed approach easily lends itself to further engineering opportunities and has the potential to be broadly deployable.